Effects of an amino acid-carbohydrate drink on exercise performance after consecutive-day exercise bouts - Skillen, R. A.; Testa, M.; Applegate, E. A.; Heiden, E. A.; Fascetti, A. J.; Casazza, G. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
This study examined the effect of amino acids in a carbohydrate beverage on cycling performance. Twelve male athletes (28.5 ± 2.1 yr) cycled at 75% VO2peak for 90 min followed by a ride to exhaustion at 85% VO2peak, before (T1) and on 2 consecutive days (T2 and T3) after 2 weeks of supplementation with 3.6% carbohydrate plus 1% amino acids (AA) or 4.6% carbohydrate-only (CHO) isocaloric beverages. Muscle damage was assessed by plasma creatine kinase (CK), and muscle fatigue by changes in vertical jump pre- to postexercise. Muscle soreness, overall fatigue, and changes in mood state were assessed using questionnaires. Plasma CK was lower for AA in T3 (214.0 ± 13.5 vs. 485.9 ± 191.4 U/L immediately post, 213.9 ± 13.1 vs. 492.0 ± 199.4 U/L 5 hr post, and 194.9 ± 17.9 vs. 405.9 ± 166.6 U/L 24 hr postexercise in AA and CHO, respectively). Time to exhaustion decreased from T2 to T3 only in CHO (10.9 ± 2.5 to 12.6 ± 3.2 vs. 13.8 ± 2.8 to 7.8 ± 1.5 min in AA and CHO, respectively). Vertical-jump change from pre- to postexercise was greater in T3 for the CHO treatment. Total fatigue score and mood disturbance decreased significantly only with AA in T3. The addition of AA to a carbohydrate beverage after consecutive-day exercise bouts reduced muscle damage as indicated by CK levels, decreased fatigue, and maintained exercise performance compared with consuming carbohydrate alone.